Automatic Pedestrian Safety in Automobiles through Microcontroller and RF Technology - A., Suguna; B., Achiammal; S., Daniel Vasanthan; V., Chandan Vignesh K (Journal of Ubiquitous Computing and Communication Technologies, 2024)
One of the government's top priorities for creating a safe driving environment is pedestrian safety. To guarantee safety in all respects, many safety measures have been put into place by the government and adopted by the populace. The main goal of this study is to indirectly lower the number of accidents by eliminating their core causes. Careless driving and excessive speeding are the main causes of accidents. This document ensures that a car is designed to travel at a specific pace in each area, keeping it within safe speed limit. This lessens the impact of accidents, including material and human loss. This is accomplished by using the proper microcontroller, RF transmitter, and receiver through a comparison process. The car equipped with a receiver, receives the data signal from the traffic sign board, compares it to the output, and adjusts the speed of the vehicle to a safe level. By doing this, the car is always forced to go at the designated speed, and driving behaviour is altered, reducing the likelihood of accidents. This offers a supplementary safety precaution that focuses on eliminating the primary sources of mishaps.
Keywords: Speed Sensor; RF Transmitter Receiver; IR sensor